Improving Ability to Recognize Hijaiyah Letters through Flash Cards in Early Childhood - Duwi Meilina (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2022)
This research explores the effort to enhance Arabic letter recognition using Flash Cards among early childhood learners at RA Nurul Iman in Tanjung Bulan Village, Kasui District, Way Kanan Regency, Lampung. The findings clearly demonstrate the positive impact of the flash card media on hijaiyah letter recognition within Group B children. The overall average percentage gain of 70.46% aligned with the